Shape memory effect in radiation grafted ion exchange membranes - Henkensmeier, Dirk; Gubler, Lorenz (Royal Society of Chemistry, 2014)
When swollen radiation grafted ion exchange membranes are dried in a fixed geometry, e.g. by clamping on a frame, dry membranes memorise the wet shape and show reduced area swelling and increased swelling in the thickness direction upon rehydration. In one case, the ratio thickness/area swelling increased from 0.6 to 35.